Treatment of congenital anomalies in a missionary hospital inBangladesh: results of 17 paediatric surgical missions - Del Rossi, C.; Fontechiari, S.; Casolari, E.; Fainardi, et al., V. (Acta Biomedica Atenei Parmensis, 2009)
Background and aim of the work: We report 17 years of experience in a missionary hospital with decreased facilities in Bangladesh. Our interest  was directed at children with congenital malformations since they live in a society where the exclusion of abnormal children is common. A better treatment for these children offers them a better future. Materials and methods: Bangladesh is among the most densely populated countries in the world: its population ranges from 142 to 159 million, and it is one of the poorest nations in the world. From 1991 to 2008 our Italian pediatric surgical team performed 17 5 weeks missions in a missionary hospital in Khulna, Bangladesh, during the months of January and February. Results: A total of 1556 patients underwent surgery, mostly for severe congenital anomalies. The infection rates were very low: 2-3%; the mortality rate was 0,4% for all the operations. Conclusions: Good pre-operative preparation and assistance, assurance of cyclical follow-up and a trained surgical team allowed the successful treatment of complex malformations in a missionary hospital with modest services.